Rickettsia amblyommatis in Ticks: A Review of Distribution, Pathogenicity, and Diversity - Elise A. Richardson; R. Michael Roe; Charles S. Apperson; Loganathan Ponnusamy (Microorganisms, 2023)
Rickettsia amblyommatis is a potentially pathogenic species of Rickettsia within the spotted fever group vectored by ticks. While many studies have been published on this species, there is debate over its pathogenicity and the inhibitory role it plays in diagnosing illnesses caused by other spotted fever group Rickettsia species. Many publications have recorded the high infection prevalence of R. amblyommatis in tick populations at a global scale. While this species is rather ubiquitous, questions remain over the epidemiological importance of this possible human pathogen. With tick-borne diseases on the rise, understanding the exact role that R. amblyommatis plays as a pathogen and inhibitor of infection relative to other tick-borne pathogens will help public health efforts. The goal of this review was to compile the known literature on R. amblyommatis, review what we know about its geographic distribution, tick vectors, and pathogenicity, assess relatedness between various international strains from ticks by phylogenetic analysis and draw conclusions regarding future research needed.